2015
DOI: 10.4236/ijcm.2015.612126
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hormonal Receptors Estrogen Receptor, Progesterone Receptor and Her-2/Neu with Tumor Characteristics in Breast Carcinoma: Study of 100 Consecutive Cases

Abstract: Introduction-Breast cancer is the most common cancer and leading cause of death in women. In India, its incidence is rapidly rising over last few decades. Present study is aimed to study the pattern of expression of hormonal receptors and Her-2/neu in invasive breast carcinoma and to correlate estrogen receptor (ER), progesterone receptor (PR) and Her-2/neu expressions with various clinicopathological parameters. Material and methods: The present study was carried out in Department of Pathology, S.C.B. Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 4 publications
2
12
1
Order By: Relevance
“…32 Considering the grade of tumour and hormonal receptors, mostly patients were of grade 2 and were hormonal receptors positive which is in concordance with study by Baswal et al 33 In our study there were no grade 1 tumours while in other studies (Table 4), there were cases of grade 1 and those were again hormonal receptors positive. While in the study by Biswal et al, 33 there were also no grade 1 tumors. In our study grade 3 tumours were either triple negative, triple positive or Her2Neu positive which is again in concordance with other studies (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…32 Considering the grade of tumour and hormonal receptors, mostly patients were of grade 2 and were hormonal receptors positive which is in concordance with study by Baswal et al 33 In our study there were no grade 1 tumours while in other studies (Table 4), there were cases of grade 1 and those were again hormonal receptors positive. While in the study by Biswal et al, 33 there were also no grade 1 tumors. In our study grade 3 tumours were either triple negative, triple positive or Her2Neu positive which is again in concordance with other studies (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Most of patients (92%) show tumor size of more than 2 cms. Priydarshini Biswal et al [4] Azizum Nisa et al [5] Moses et al [6] and Rashed,Mona M [7] also concluded similar trend in age and tumor size distribution. Sepideh et al [8] show 65% cases of less than 1 cms tumor size.…”
Section: Discussionmentioning
confidence: 85%
“…Present study show 47.5% ER positive cases and 37.5% PR positive cases. Study of Priydarshini et al[4] show 40% ER positive and 32% PR positive cases. ER and PR expression is greater in histopathological grade I patients as compared to histopathological grade II.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Total 50% of cases out of all PR negative cases were diagnosed in stage 2 nd of the disease and 52% of all PR positive cases were diagnosed in stage 2 nd of the disease (Table 2). Among the 12 cases with HER 2 receptor negative status, majority (7) were diagnosed at grade 3 or above and also among the HER 2 receptor positive cases majority were diagnosed in grade 3 or above of the disease (Table 2). Among ER status negative cases 18 (62%) out of total 29 cases were diagnosed in grade 3 or above of the disease and among the ER positive cases also majority were diagnosed at grade 3 or above of the disease (50% out of total 54 cases) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%